Perjuangan Kemerdekaan Palestina - Hafizh Sahashika Sudantha, Muhammad; Sidik, Hasan (Indonesia Center for Middle East Studies, 2024)
The Israeli-Palestinian conflict, which began with the Balfour Declaration of 1917 and UN Resolution 181 of 1947 that facilitated the establishment of the state of Israel in 1948 by occupying part of the Palestinian territory, reflects a long struggle for a claim to territory and sovereignty. The existence of Israel as an occupying power encourages the Palestinian people's efforts to achieve absolute independence. From this effort emerged Fatah and Hamas as two main political forces that offer opposing approaches to dealing with Israel. This research uses qualitative methods. The research results show that the struggles of Hamas and Fatah have different methods, where Fatah prioritizes diplomatic strategies, and Hamas chooses a coercive approach. In addition, the two have a shared national interest, namely achieving independence. However, internal rivalry between the two worsens the prospects for Palestinian independence, regardless of the choice of approach used.